Efektivitas Pemberian Kombinasi Parasetamol 2 mg/kgBB dan Propofol Mct/Lct terhadap Pengurangan Nyeri Penyuntikan - Fuyanto, Indra; , Zulkifli; Haloho, Agustina Br. (Perdatin Pusat, 2014)
Propofol adalah obat anestesi yang paling banyak digunakan dan sering menimbulkan nyeri saat penyuntikan. Nyeri ini menempati posisi ketiga kondisi yang tidak diinginkan. Ada 2 macam propofol yaitu propofol LCT dan propofol MCT/LCT. Parasetamol adalah obat analgetik yang aman untuk semua usia dan dapat mengurangi nyeri penyuntikan propofol. Penelitian ini bertujuan untuk mengetahui efektivitas penambahan parasetamol 2 mg/kgBB terhadap pengurangan nyeri penyuntikan propofol. Uji klinik acak berbanding buta ganda dilakukan di RSUP Dr. Mohammad Hoesin Palembang pada bulan Februari–April 2014. Sampel 99 orang dan dibagi dalam tiga kelompok. Penelitian pada skor nyeri, rasa nyeri, dan kualitas nyeri menggunakan skor VAS. Analisis menggunakan uji-t, One Way Anova dan post hoc dengan program SPSS versi 20. Uji-t menunjukkan sampel penelitian bersifat homogen. Uji One Way Anova menunjukkan perbedaan skor nyeri, rasa nyeri dan kualitas nyeri antar ketiga kelompok perlakuan. Uji post hoc didapatkan kelompok P memiliki skor nyeri yang lebih rendah dibandingkan dengan kelompok L dan M secara bermakna. Kelompok P tidak memiliki perbedaan rasa nyeri dan kualitas nyeri yang bermakna dibandingkan dengan kelompok M. Penambahan parasetamol 2 mg/kgBB terbukti efektif mengurangi nyeri penyuntikan propofol. Kata kunci: Nyeri, parasetamol, propofol, uji klinik acak berbanding Propofol is the most widely used as anesthetic drug in general anesthesia. Pain while propofol was given, has already ranked in third place as many patients complain of pain during the injection. There are two types of propofol which is available: propofol LCT and propofol MCT/LCT. Paracetamol is known as analgesics drug which is safe for all ages and can be used to reduce the pain of propofol injection. The aim of this study was to determine the efficacy of reducing the pain of propofol injection by the addition of paracetamol 2 mg/kgBW. Randomized controlled trial, double blind has been conducted at Dr. Mohammad Hoesin Palembang hospital from February to April 2014. There were 99 samples that divided into three groups. The groups were L group, M group and P group. The research is about pain scores, pain, and quality of pain. Measurement of pain using the VAS score. Data is analyzed with t-test, One Way Anova, and Post Hoc test using SPSS program 20.00 version. T-Test showed that the respondents were homogeneous in all groups. One Way Anova test showed the differences in pain scores, pain and quality of pain among all groups. Post Hoc test showed that P group has lower pain scores differences than L group and M group significantly. It can be concluded that the addition of paracetamol 2 mg/kgBW before propofol injection can reduce the pain caused by the injection. Reference Key words: Pain, paracetamol, propofol, randomized controlled trial Reves JG, Glass PSA, Lubarsky DA, McEvoy MD, Ruiz RM. Intravenous Anesthetics. Dalam: Miller RD, penyunting. Miller’s Anesthesia. Edisi ke-7. California: Elsevier; 2009. hlm.719–68. Evers AS, Crowder M, Balser JR. General Anesthetics. Dalam: Brunton LL, penyunting. Goodman & Gilman’s The Pharmacological Basis of Therapeutics. Edisi ke-12. New York: McGraw-Hill; 2011. hlm. 501–36. Kumar P. Propofol. 2013 (diunduh 2 Oktober 2013). Tersedia dari: http://www.anaesthesia.co.in. Wijeysundera DN, Kavanagh BP. Prevention of pain from propofol injection: adequately studied, but inadequately managed. Br Med J. 2011.hlm. 667–8. Sethi N, Jayaraman L, Sethi M, Sharma S, Sood J. Prevention of propofol pain: a comparative study. Middle East J Anaesthesiol. 2009. hlm. 71–4. Zahedi H, Maleki A, Rustami G. Ondansentron pretreatment reduces pain on injection of propofol. Acta Med Iran. 2012. hlm. 239–43. Zhao GY, Guo Y, Bao SM, Meng LX, Zhang LH. Prevention of propofol induced pain in children: pretreatment with small doses of ketamine. J Clin Anaesth. 2012.hlm.284–8. Yadav M, Durga P, Gopinath R. Role of steroids in prevention of pain on propofol injection. J Anaesth Clinic Res. 2011. hlm.132–5. Kwak HJ, Min SK, Kim JS, Kim JY. Prevention of propofol induced pain in children: combination of alfentanil and lidocaine vs alfentanil or lidocaine alone. Br J Anaesth. 2009. hlm. 410–2. Borazan H, Erdem TB, Kececioglu M, Otelcioglu S. Prevention of pain on injection of propofol: a comparison of lidocaine with different doses of paracetamol. Euro Soc Anaesthesiol. 2010. hlm. 253–7. Ozkan S, Sen H, Sizlan A, Yanarates O, Mutlu M, Dagli G. Comparison of acetaminophen (with or without tourniquet) and lidocaine in propofol injection pain. Bullet Clin Psychopharmacol. 2011. hlm.100–4. Demir A, Aydinli B, Tezcan B, Ucar P, Ince D, Oztuna D, dkk. Influence of temperature and pH changes on propofol injection pain. Turk J Anaesth Reanim. 2013;p34–7. Beyaz S, Tufek A, Tokgor O. The effect of propofol lipuro with and without lidocaine on injection pain in children. Niger J Clin Practice. 2011. hlm. 60–4. Zahoor A, Ahmed N. The effects of duration of propofol injection on hemodynamics. M E J Anesth. 2010. hlm. 845–50. Dewhirst E, Lancaster C, Tobias JD. Hemodynamic changes following the administration of propofol to facilitate endotracheal entubation during sevoflurane anesthesia. Int J Clin Exp Med. 2013.hlm. 26–9. Nyman Y, Hofsten KV, Georgiadi A, Eksborg S, Lunnqvist PA. Propofol injection pain in children: a prospective randomized double blind trial of a new propofol formulation versus propofol with added lidocaine. Br J Anaesth. 2009. hlm. 222–5. Nyman Y, Hofsten KV, Eksborg PS, Lonnqvist PA. Etomidate-lipuro is associated with considerably less injection pain in children compared with propofol with added lidocaine. Br J Anaesth. 2009. hlm. 536–9. Schaub E, Kern C, Landau R. Pain on injection: a double blind comparizon of propofol with lidocaine pretreatment versus propofol formulated with long and medium chain triglyserides. Anaesth Analg. 2009. hlm. 699–702. Canbay O, Celebi N, Arun N, Karagoz AH, Saricaoglu F, Ozgen S. Efficacy of intravenous acetaminophen and lidocaine on propofol injection pain. Br J Anaesth. 2009. hlm. 95–8. Ohmizo H, Obara S, Iwama H. Mechanism of injection pain with long and long medium chain triglyceride emulsive propofol. Canad J Anesth. 2009. hlm. 595–9.